Stone statues of Saryarka: research and analysis (Journal of history, 2022)
The paper presents the results of a study of ancient and medieval stone sculptures that adorn the wide steppes of Saryarka. The article is devoted to the problem of the need for research and a complete analysis of the stone sculptures of Saryarka. The first scientific information about stone statues was collected by Ch. Valikhanov while studying the mausoleum of Kozy Korpesh – Bayan Sulu during his travels around Issyk-Kul. A. Kh. Margulan in his writings presented serious scientific studies of the monumental monuments of Saryarka. Along with this, A. Kh. Margulan and L. R. Kyzlasov jointly analyzed the stone sculptures attributed to the monuments of medieval nomads, which were discovered on the banks of the Zhangabyl River. From the mid-1950s to the early 1980s, researcher M.K. Kadyrbaev was engaged in the study of ancient and medieval stone sculptures in Central Kazakhstan. The article also analyzes the history of the modern stage of the study of Saryarka stone sculptures. In the last decade, the chronological framework for studying the stone sculptures of Saryarka has been expanding. At present, the scientist A. Z. Beisenov in his works touches upon topical issues related to stone sculptures and stellations of the Saka period of Saryarka, is engaged in a comprehensive study of the complexes in which they are located. Since 2009, A. M. Dosymbaeva has also been working on a comprehensive analysis of medieval stone sculptures of Northern Saryarka.